Climatic and anthropic effects in the morphogenesis of Guarumal Island, Térraba-Sierpe National Wetland, Costa Rica - Quesada-Román, Adolfo (2017)
A study was conducted on the climatic and anthropic implications during 64 years of changes (1948-2012) in the morphology of Guarumal Island in the Térraba-Sierpe National Wetland, southeast of Costa Rica. By 1948 the island did not exist; there was only a shallow development of some sandbars in Guarumal mouth. However, from 1972 to 1992 the Guarumal Island increased its size and settled its base gradually; and it is from 2012 when the vegetation further strengthens this landform. The causes related with the island formation and its development are climate variability (ENSO phenomena)—with greater sedimentation pulses during periods of La Niña)—changes in tidal patterns, as well as land-use changes from forests to pastures or agricultural zones next to the wetlands, and in the watersheds that drain into this delta, such as the Térraba and Sierpe rivers. This global trend of modification of the coastal geoforms, produced by the climatic variations and the environmental impacts resulting from the human activities, are discussed based on the results obtained in the Térraba-Sierpe delta.